2016
DOI: 10.1159/000447488
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Retroperitoneal Liposarcoma Encasing the Entire Left Kidney and Adherent to Adjacent Structures: A Case Report

Abstract: Retroperitoneal liposarcoma is a rare tumor. The dimension and weight of liposarcoma are variable; those over 20 kg are called ‘giant liposarcoma’. Herein, we report giant retroperitoneal liposarcoma measuring 45 cm in diameter and 25 kg in weight encasing the entire left kidney and adherent to adjacent structures. A 71-year-old woman presented for a regular checkup. Image study revealed a huge mass probably indicative of retroperitoneal liposarcoma encasing the entire left kidney and adherent to adjacent stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…A RLS tumor that encases the kidney is a relative indication for nephrectomy. In this case, kidney conservation may be attempted but there is always a risk of incomplete resection [11,12] . Some authors reported an en-bloc resection of the RLS with kidney and showed that there was no histologic tumoral involvement of the kidney [13,14] as was the case of our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A RLS tumor that encases the kidney is a relative indication for nephrectomy. In this case, kidney conservation may be attempted but there is always a risk of incomplete resection [11,12] . Some authors reported an en-bloc resection of the RLS with kidney and showed that there was no histologic tumoral involvement of the kidney [13,14] as was the case of our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding nephrectomy seems also possible when the RLS is widely displacing the kidney [4,16] . In addition to these criteria, the patient's advanced age is another argument for trying to preserve the kidney [11] . An ureter encasement is not a formal indication for nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions and weight of liposarcomas are variable, and they may get to large in the retroperitoneal space [5].…”
Section: Discussionmentioning
confidence: 99%
“…Retroperitoneal liposarcoma often appears as an asymptomatic abdominal mass, or patients may present symptoms caused by the effect of the growing mass on adjacent structures [3] . The dimensions and weight of liposarcomas are variable, and they may get to large in the retroperitoneal space [5] .…”
Section: Discussionmentioning
confidence: 99%
“…In English literature, from 1975 to Octobor 2016, only 13 cases of giant RPLS have been reported (Table 1). [6][7][8][9][10][11][12][13][14][15][16][17][18] Of the 14 patients (including ours), there were 9 male (64.3%) and 5 female (35.7%) with a median age of 53 (39-72) years and they all presented atypical clinical manifestations such as abdominal distention or increasing in abdominal girth. All the 14 giant RPLS were diagnosed by CT scan.…”
Section: Reviewmentioning
confidence: 99%